ProSoftware: uma extensão da modelagem de processos de negócio voltada para o desenvolvimento de software - Elayne Ferreira de Souza (2012)
The lack of knowledge about the requirements that the software must adequately support in order to be effectively used within organization is a major cause of changes and failures in software development projects. Business process modeling has been acknowledged by both researchers and practitioners as an important approach to helpimproving software development projects. However, most of the solutions involving business process modeling focus on the capture and support of functional aspects and little attention is usually given to the characterization of actors regarding their motivation and needs and to the modeling of certain important aspects of their executed activities.This work proposes an extension to a method of business process modeling focused on software development, called ProSoftware. The work is based on Activity Theory and analysis techniques from the context of Software Engineering and Usability: Persona and Scenario. The main focus of this approach is a better understanding of human activities.The objectives of ProSoftware are to define a business modeling related process for the analysis of non-functional characteristics of business activities; the identification of a set of historical, cultural and motivational information of human activities, the identification of points of conflict between the actors and business processes, contrasting differences between business goals and the interests of the actors of the organization, and the identification of human preferences or tools that can bring benefits or risks to the business. The proposed method can help systems analysts to better understanding the needs of the organization and, therefore, propose software solutions that will be aligned with business process needs.